Representasi Figur Burung Garuda yang Digunakan sebagai Lambang Negara - Oentoro, Yurica (Institute of Research and Community Outreach - Petra Christian University, 2012)
There are three coat of arms which have high level of similarities, such as Indonesia, Romania, and United Arab Emirates. These three nations the use bird figure as their coat of arms. These three nation’s perception for the meaning of the bird is same. However, the depiction of the bird’s form is different for each nation. It’s because each nation is using a different species of birds. The differences in perception also includes what is shown in the coat of arms. This research used Visual Methodologies from the site of image itself with compositional interpretation and Peirce’s semiotics to analyze these three coat of arms. The purpose of this research is to know the meaning behind the three coat of arms which have high level of similarities.